PENGARUH DANA OTONOMI KHUSUS TERHADAP INDEKS PEMBANGUNAN MANUSIA KABUPATEN/KOTA DI PROVINSI ACEH - Muhammad Hijrah Saputra (Universitas Negeri Medan, 2014)
This study aimed to determine the effect of the Special Autonomy Fund AgainstHuman Development Index in Aceh, to achieve these objectives, this study uses the Human Development Index (HDI) as the dependent variable and the SpecialAutonomy Fund (Autonomy) as independent variables. The data analyzed in thisstudy are secondary data from the reports on the realization of the Government's budget 23 districts / municipalities in the province of Aceh which was obtained through a survey BAPPEDA Aceh and the Central Statistics Agency (BPS) of Aceh. The data used are panel data which is a combination of Time Series and Cross Section. Data time series used is the 23 districts / cities in the period 2009 - 2012. The method used in this study is one of three in a panel data analysis techniques that pool (common) effect model, fixed effect model and random effect model. Based on data processing studies concluded that the SAF has a positive and significant effect on the Human Development Index, which the SAF increase in tandem with the increase in the Human Development Index. So it can be concluded that the increase in SAF positive effect on the Human Development Index in 23 districts / municipalities in the Aceh Province.